2021
DOI: 10.1111/1745-9133.12537
|View full text |Cite
|
Sign up to set email alerts
|

The online behaviors of Islamic state terrorists in the United States

Abstract: This study offers an empirical insight into terrorists' use of the Internet. Although criminology has previously been quiet on this topic, behavior-based studies can aid in understanding the interactions between terrorists and their environments. Using a database of 231 US-based Islamic State terrorists, four important findings are offered: (1) This cohort utilized the Internet heavily for the purposes of both networking with co-ideologues and learning about their intended activity. (2) There is little reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(64 reference statements)
3
10
0
Order By: Relevance
“…First, the majority of individuals convicted of extremist offences within this study were found to have radicalized through both online and offline means (48%, compared with Internet -12% and Face-to-face -40%). This finding is consistent with other studies focusing on individuals convicted of extremist offences in other countries (see Whittaker, 2021), suggesting that most operate across both the online and offline domains.…”
Section: Summary Of Findings and Key Insightssupporting
confidence: 93%
See 1 more Smart Citation
“…First, the majority of individuals convicted of extremist offences within this study were found to have radicalized through both online and offline means (48%, compared with Internet -12% and Face-to-face -40%). This finding is consistent with other studies focusing on individuals convicted of extremist offences in other countries (see Whittaker, 2021), suggesting that most operate across both the online and offline domains.…”
Section: Summary Of Findings and Key Insightssupporting
confidence: 93%
“…The role of the Internet in radicalization and offending of those who commit extremist offences has become a central part of contemporary cases of terrorism (Whittaker, 2021). However, when considering the threat of online radicalization, it has yet to be established which characteristics, of individuals and offences, indicate different levels of risk and vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research conducted on the same dataset, (Whittaker, 2021) analysed the online behaviours of 231 IS terrorists in the US. The study finds that 92% of terrorists use the Internet for some purpose, but that those used the Internet to either engage with co-ideologues or plan their activity online were significantly more likely to do so offline as well, further lending weight to the argument made by Gill et al (2017) that separating the two domains is a false dichotomy.…”
Section: Previous Researchmentioning
confidence: 99%
“…At first glance, it is apparent that terrorists use the Internet in high numbers for a range of antecedent behaviours. In fact, research conducted in a more recent timeframe suggests that the use of the Internet may be increasing (Gill et al, 2017;Bastug, Douai and Akca, 2018;Whittaker 2021). However, these pieces of research show that the Internet is not a cause, but rather a facilitator of engaging in terrorist activity.…”
Section: Previous Researchmentioning
confidence: 99%
“…The figures from Gill et al (2015) are roughly confirmed by Whittaker (2021) who used a data set on 231 U.S. based Daesh (IS) terrorists, all that were recorded during the period 2010 to 2020, and their online activities. Some online activity was found to be present in 92% of all cases; more than 80% interacted online with co-ideologues, 80% used social media platforms for at least some of their activities, 36% had disseminated propaganda online.…”
Section: Evidence On Prevalence Of Online Radicalization and Associat...mentioning
confidence: 84%